Go with your gut : the insider's guide to banishing the bloat with 75 digestion-friendly recipes - Youkilis, Robyn (Kyle Books, distributed by National Book Network, 2016)
When nutritionist Robyn Youkilis began her coaching practice, she quickly realized that the vast majority of complaints she heard from clients were about their digestion: if your digestive system isn't functioning properly, you can gain weight and suffer from fatigue, insomnia, bloating, indigestion and IBS. This exciting new book helps to change your relationship with food and your body by focusing on what your symptoms are telling you. It includes a four-week program to build new habits into daily life at a manageable pace. Each chapter includes a quiz that helps to determine what issue affects your digestion most, and the best tips and tricks to combat these roadblocks. Part two includes 75 delicious yet simple recipes to help you on that path. Go With Your Gut will help you become your healthiest self.